Association between consumption of ultra-processed foods and beverages with nutritional status of private senior high school students in Pontianak, West Kalimantan, Indonesia - Septiana Maria Deba Ginting; Judhiastuty Februhartanty; Helda Khusun (World Nutrition Journal, 2024)
Background: Many low- and middle-income countries are now facing the “double burden” of malnutrition, one of them is overweight/obesity. Over 340 million children and adolescents were overweight and obesity in 2016. Obesity among adolescents may increase, in part due to changes in the food system, which now offers a wide range of ultra-processed foods (UPF) that minimize preparation time. Indonesia has also a large and rapidly growing market for unhealthy drinks, which are sold in various places including schools and hospitals. Objective: This study aimed to investigate the association of UPF and beverages consumption and other related factors with nutritional status of senior high school students in Pontianak, West Kalimantan, Indonesia. Methods: This cross-sectional study conducted in Pontianak investigated the association between UPF consumption and nutritional status of SHS students. Data collection was conducted at Imanuel and Petrus SHS Pontianak in June 2023, involving 273 students from grades 10th and 11th. Weight and height measurement was obtained for calculating the BMI for age Z-scores, while UPF and beverages consumption was obtained by FFQ. Structured questionnaire, 24-hours recall, and IPAQ-S were used for assessing sociodemographic status, Total Energy Intake and Physical Activity Level. Data analysis used SPSS version 26. Results: The result found 40.3% of students were overweight-obesity; 51.6% consumed excessive UPF and beverages. It showed an inverse association between UPF consumption and nutritional status. The study identifies UPF and beverages consumption, gender, mother's education level, and family income as factors associated with nutritional status among adolescents. Conclusion: The consumption of ultra-processed Foods was high, with the highest UPF intake came from snacks and sweets (22.4%). There was inverse association between UPF and beverages consumption with nutritional status. There was also significant association between UPF and beverages, gender, mother education level and family income with nutritional status.